2019
DOI: 10.21037/atm.2019.06.48
|View full text |Cite
|
Sign up to set email alerts
|

Variable clinical features and genotype-phenotype correlations in 18 patients with late-onset Pompe disease

Abstract: Background: Pompe disease is a lysosomal storage disorder caused by the deficiency of enzyme acid alphaglucosidase (GAA) which results in accumulation of glycogen, particularly in the skeletal, cardiac, and smooth muscles. The late-onset form with symptoms presenting in childhood through adulthood, is characterized by proximal muscle weakness, respiratory insufficiency, and unlike the infantile-onset form often with no cardiac involvement. Methods: We report our experience with 18 adult patients (14 males/4 fe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
32
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(36 citation statements)
references
References 51 publications
0
32
0
2
Order By: Relevance
“…The emerging new features of the disease include vascular and cerebrovascular defects, for example, intracranial aneurysm or dilative arteriopathy, hearing loss, central and peripheral nervous system abnormalities, scoliosis, progressive loss of bone mass, as well as gastrointestinal and urinary tract symptoms [40] (reviewed in [41]). A small subset of LOPD patients develop cardiomyopathy which improves on ERT [42].…”
Section: An Expanded Set Of Clinical Characteristicsmentioning
confidence: 99%
“…The emerging new features of the disease include vascular and cerebrovascular defects, for example, intracranial aneurysm or dilative arteriopathy, hearing loss, central and peripheral nervous system abnormalities, scoliosis, progressive loss of bone mass, as well as gastrointestinal and urinary tract symptoms [40] (reviewed in [41]). A small subset of LOPD patients develop cardiomyopathy which improves on ERT [42].…”
Section: An Expanded Set Of Clinical Characteristicsmentioning
confidence: 99%
“…Eight cohort studies performed cardiac imaging and/or function tests using TTE, one study did not report what type of diagnostic modality was used [31]. Most commonly reported findings were various valvular abnormalities/dysfunction (VA/VD), LVH and decreased ejection fraction (dEF).…”
Section: Cardiac Findings In Cohort Studiesmentioning
confidence: 99%
“…One study reported two children with a hypertrophic cardiomyopathy (HCM), both patients did not carry the common IVS1 mutation and had a very early onset of Pompe disease symptoms (before the age of 1) [25]. One study reported three adults (aged 22, 40 and 42 years) with cardiomyopathy (unspecified) which improved with ERT, of whom one had a childhood onset of Pompe disease and did not carry the common IVS1 mutation [31].…”
Section: Cardiac Findings In Cohort Studiesmentioning
confidence: 99%
“…Сколиоз чаще развивается у детей с БП, реже у взрослых [34]. По данным Регистра Помпе, он выявляется у 24,8 % больных [35] и вносит отрицательный вклад в дыхательную функцию грудной клетки.…”
Section: лекции и обзорыunclassified
“…Снижение слуха у больных с БППН, по одним данным, не превышает число случаев в общей популяции [45], близкие данные приводят и другие исследователи [46]. Из 20 пациентов в 57 % случаев выявлена нейросенсорная и в 33 % -кондуктивная тугоухость [47].…”
Section: лекции и обзорыunclassified